Social Capital and Populism in the Philippines: The Case of Duterte - Fernandez, Artchil (Social Sciences and Development Review, 2023)
The paper tackles the question – are the high performance and trust ratings of President Rodrigo R. Duterte (PRRD) indicative of a deep and abiding social capital existing between state and society, and if so, does this mean that Filipinos will now move away from myopic to enlightened self-interest in addressing the current challenges that the country faces? It interrogates the question through the lens of Putnam’s concept of social capital. The paper discusses Putnam’s notion of social capital, Duterte’s high performance and trust ratings, and whether they are linked. The study likewise explores the broader connection between populism and social capital.